1966
DOI: 10.1111/j.1365-2141.1966.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Methylmalonic Acid Excretion in Vitamin B12 Deficiency

Abstract: methylmalonic acid was first isolated from pooled human urine in 1957 by Thomas and Stalder and convincing evidence has since been obtained to show that in man the isomerization of l‐methylmalonyl‐Co A to succinyl‐Co A is dependent on the B12 coenzyme dimethylbenzimidazolyl cobamide (White, 1962). Indeed, Cannata, Focesi, Mazumder, Warner and Ochoa (1965) showed recently that l‐methylmalonyl‐Co A mutase bears two molecules of cobamide coenzyme firmly attached to its molecule. In a series of 30 patients Cox and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 12 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…Previous investigators have shown that most patients with cobalamin (Cbl, vitamin B12)' deficiency have elevated levels of methylmalonic acid in their urine (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The origin of the methylmalonic acid has recently been elucidated (13) and is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators have shown that most patients with cobalamin (Cbl, vitamin B12)' deficiency have elevated levels of methylmalonic acid in their urine (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The origin of the methylmalonic acid has recently been elucidated (13) and is illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…More rarely, diagnostic problems can also develop in patients with hematologic abnormalities, since serum Cbl levels may be normal in Cbl-deficient patients who have elevated levels ofCblbinding proteins (24). Additional diagnostic tests like urinary methylmalonic acid (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and the deoxyuridine suppression test (25,26) have not been widely used and, thus, a definite need exists for additional tests that could be used to evaluate patients for Cbl deficiency and to evaluate the sensitivity and specificity of the serum Cbl assay.…”
Section: Introductionmentioning
confidence: 99%
“…The patient and control cases were loaded orally with 3g of valine14 and 24 hour-urine was collected and analyzed for methylmalonic acid by thin layer chromatography described by Bashir et al 15 The urinary excretion of methyl malonic acid was detectable in the present patient, but not in control cases. …”
Section: Urinary Excretion Of Methylmalonic Acidmentioning
confidence: 65%
“…Consequently, methylmalonic acid may be excreted in increased quantities in the urine in conditions associated with deficiency of the coenzyme, such as pernicious anaemia, dietary depletion of the vitamin, or a metabolic block in the synthesis of this derivative (Cox and White, 1962;Bashir et al, 1966;Rosenberg et al, 1968). This increase is accentuated by the oral administration of metabolic precursors of methylmalonic acid (Gompertz et al, 1967), and a number of studies have now demonstrated the usefulness of urinary methyl malonic acid determinations after valine loading in the diagnosis of cobalamin deficiency (Green and Pegrurn, 1968;Gutteridge and Wright, 1970;Dale, 1972).…”
mentioning
confidence: 99%
“…Methylmalonic acid has been determined in urine by gas chromatography (Cox and White, 1962;Gornpertz et al, 1967), thin-layer chromatography Methods and materials (Bashir et al, 1966;Dreyfus and Dube, 1967;Gutteridge and Wright, 1970), and a colorimetric For the loading test, 10 g L-valine was administered method based on a coupling reaction with diazotised orally as a solution in approximately 250 ml orange p-nitroaniline (Giorgio and Plaut, ]965). The gas juice.…”
mentioning
confidence: 99%